2022
DOI: 10.1097/mat.0000000000001692
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Pulmonary Artery Cannulation to Treat Acute Secondary Right Heart Failure While on Veno-venous Extracorporeal Membrane Oxygenation

Abstract: Right heart failure (RHF) is a common, yet difficult to manage, complication of severe acute respiratory distress syndrome requiring extracorporeal membrane oxygenation (ECMO) that is associated with increased mortality. Reports of the use of percutaneous mechanical circulatory support devices for concurrent right heart and respiratory failure are limited. This series describes the percutaneous cannulation of the pulmonary artery for conversion from veno-venous to veno-pulmonary artery return ECMO in 21 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The median time from V-V ECMO initiation to conversion to V-PA ECMO was 12 (8.5–23.5) days, and survival to hospital discharge was only 25%. 31 These data indicate that application of V-PA ECMO in advanced RV injury and despite V-V ECMO support may not significantly alter outcomes. Perhaps pre-emptive V-PA ECMO or application of V-PA ECMO in ARDS patients with RV injury phenotypes where the RV meets flow demand, that is, before RV failure and secondary organ injuries develop, would make more physiologic sense; this notion, however, should be supported by prospective randomized data.…”
Section: Veno-pulmonary Arterial Ecmo and Ards Cardiorespiratory Phen...mentioning
confidence: 82%
See 3 more Smart Citations
“…The median time from V-V ECMO initiation to conversion to V-PA ECMO was 12 (8.5–23.5) days, and survival to hospital discharge was only 25%. 31 These data indicate that application of V-PA ECMO in advanced RV injury and despite V-V ECMO support may not significantly alter outcomes. Perhaps pre-emptive V-PA ECMO or application of V-PA ECMO in ARDS patients with RV injury phenotypes where the RV meets flow demand, that is, before RV failure and secondary organ injuries develop, would make more physiologic sense; this notion, however, should be supported by prospective randomized data.…”
Section: Veno-pulmonary Arterial Ecmo and Ards Cardiorespiratory Phen...mentioning
confidence: 82%
“…Current V-PA ECMO literature is limited to observational data (Table 1). [23][24][25][26][27][28][29][30][31][32] A recent systematic review of five observational studies including 194 patients with coronavirus disease 2019 (COVID-19)related ARDS receiving V-PA ECMO showed that application of V-PA ECMO, using single-site dual-lumen RA-to-PA cannula was associated with high survival rates. 32 Veno-pulmonary arterial ECMO was also associated with reduced incidence of acute kidney injury (AKI) and need for renal replacement therapy (RRT).…”
Section: Evidence For Veno-pulmonary Arterial Ecmo In Ardsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of them is that it drains only from the superior vena cava, making it harder to place it correctly in shorter patients. Additionally, it is more expensive than a standard ECMO cannula; the cost is estimated to be more than USD 20,000 [ 47 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%